PEMAHAMAN DAN PELAKSANAAN NILAI-NILAI AKUNTANSI SYARIAH PADA PRAKTISI PEGADAIAN SYARIAH (STUDI KASUS PADA PT. PEGADAIAN SYARIAH SE-KABUPATEN TAPANULI BAGIAN SELATAN) - Windari Windari (AL-QARDH, 2018)
This study aims to determine the understanding and implementation of Islamic accounting values in sharia pawnshop practitioners. Data sources used by all employees of PT. Pegadaian Syariah District of South Tapanuli with a total of 14 respondents. From the results of this study, it can be understood that the humanist value of the employer is very adequate, the understanding of emancipatory value is sufficient, the understanding of Teleological value is very adequate and the understanding of Transcendental value in the employees of Islamic sharia is adequate.